THE EFFECTIVENESS OF LIFE SKILLS EDUCATION IN FOSTERING ENTREPRENEURSHIP VALUES AND INTEREST OF PRIMARY SCHOOL STUDENTS - Bachtiar Kurniawan; Muhammad Sayuti; Tri Kuat (Journal of Vocational Education Studies, 2018)
Entrepreneurship is believed as one of the pivotal attributes in a more competitive world. Therefore, early education to foster entrepreneurial values is fundamental in primary education. The purpose of this research is to find out and analyze the effect of life skills education in fostering entrepreneurship values and interest of elementary school students. Life skills education in this study cover in school entrepreneurial activities which include batik learning, cooking, and stringing. The entrepreneurship values are measured by eight indicators of self-directing, creativity, risk taking, leadership, honesty, responsibility, team work and communication. In the current study, students’ interest in entrepreneurship are indicated by four indicators of contented, affection, involvement and attention. The methods used in this research is quantitative survey research. The results of the analysis reveal that life skills education contributed to entrepreneurship values at the level of β= 0.316, t (3.377), p < 0.001 and entrepreneurship interest β= 0.202 t (2.308), p < 0.05. It can be concluded that there was contribution of life skills educational in fostering entrepreneurship values of the primary school students. The R square produced in the Model Summary is 0.115 which means that life skills education contributes 11.5% in fostering entrepreneurship values while life skills education contributes 6% of students’ interest in entrepreneurship.